2016
DOI: 10.1007/s11596-016-1544-4
|View full text |Cite
|
Sign up to set email alerts
|

Distinct expression of chemokine-like factor 1 in synovium of osteoarthritis, rheumatoid arthritis and ankylosing spondylitis

Abstract: Chemokine-like factor 1 (CKLF1) is a newly cloned chemotactic cytokine with CCR4 being its functional receptor. Recent evidence demonstrates a role of CKLF1 in arthritis. The aim of this study was to quantify the expression of CKLF1 as well as assess the correlation between CKLF1 and plasma acute-phase markers. Synovium was obtained from 16 osteoarthritis (OA), 15 rheumatoid arthritis (RA) and 10 ankylosing spondylitis (AS) patients undergoing total joint arthroplasty, with other 11 patients treated for menisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In the study of autoimmune diseases, it has been found that CMTM1 may be involved in the occurrence and development of arthritis by interacting with the C-C chemokine receptor 4 (CCR4) [19]. In addition, CMTM1 is associated with the occurrence of rheumatic diseases [20]. CMTM1 has also been reported to be highly expressed in testis, localized in spermatogonial cells, and secreted into spermatogenic tubules to participate in male reproductive activities [17].…”
Section: Discussionmentioning
confidence: 99%
“…In the study of autoimmune diseases, it has been found that CMTM1 may be involved in the occurrence and development of arthritis by interacting with the C-C chemokine receptor 4 (CCR4) [19]. In addition, CMTM1 is associated with the occurrence of rheumatic diseases [20]. CMTM1 has also been reported to be highly expressed in testis, localized in spermatogonial cells, and secreted into spermatogenic tubules to participate in male reproductive activities [17].…”
Section: Discussionmentioning
confidence: 99%
“…The second sub-pathway was the chemokine signaling pathway in the present analysis. Chemokines are crucial mediators in the inflammatory response, and in parallel, members of the chemokine system serve important roles in AS occurrence and progression ( 40 , 41 ). In addition, Chen et al ( 33 ) reported that SpA is associated with certain proinflammatory pathways, for example, the chemokine signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The ligands of CCR4 include chemokine-like factor 1 (CKLF1), CCL2, CCL3, CCL5, CCL17, and CCL22 (22,31,51,52). CKLF1 is significantly positively correlated with C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) (51). The expression of FLS in CCR4 may promote cell migration and proliferation (53).…”
Section: Ccr4 Ccr6 and Cxcr3mentioning
confidence: 99%